Роль Олександра Погорілка у становленні Харкова як міста – осередку європейської культури XIX століття - Маліков, Василь Володимирович (НТУ "ХПІ", 2016)
У статті аналізується теоретичний доробок та практичні заходи Олександра Костянтиновича Погорілка як визначного громадського діяча Харкова на межі ХІХ–ХХ століть. Його діяльність осмислюється автором у контексті процесів модернізації українського міста та засвоєння надбань тогочасної європейської цивілізації. Розкриваються соціальні, культурно-просвітницькі, гуманістичні аспекти діяльності О. Погорілка на посаді міського голови Харкова. Дослідження його подвижницької праці висвітлює ключову роль інтелігенції у розвитку міста.

The article deals with the theoretical achievements and practical measures of a prominent public figure in the late19th – early 20th centuries Alexander Pohorilko, the professor at Kharkiv technological institute, who was elected a city mayor three times in a row and successfully carried his duties for twelve years. His activities are interpreted in the context of the modernization of Ukrainian cities and the introduction and spread of the European civilization achievements and inventions. The author reveals social, cultural, educational, humanistic aspects of Alexander Pohorilko’s work as a city mayor of Kharkiv. The study of his selfless work highlights the key role of intellectuals in Ukrainian urban development of that time.
The role and significance of Alexander Pohorilko in the development of Kharkiv as the city – center of the 19th century European culture
Keywords: самоврядування; модернізація; голова міський; інтелегенція; urban development; modernization; city mayor; intellectuals